2007
DOI: 10.1074/jbc.m607383200
|View full text |Cite
|
Sign up to set email alerts
|

Insertion and Topology of Normal and Mutant Bestrophin-1 in the Endoplasmic Reticulum Membrane

Abstract: The vitelliform macular dystrophy type 2 (VMD2) gene mutated in Best macular dystrophy encodes a 585-amino acid putative transmembrane protein termed bestrophin-1. The vast majority of known disease-associated alterations are of the missense type, which cluster near predicted transmembrane domains (TMDs). To investigate bestrophin-1 membrane topology and to assess consequences of point mutations on membrane integration, we have analyzed the insertion of putative TMDs into the endoplasmic reticulum (ER) membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
82
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(88 citation statements)
references
References 42 publications
5
82
0
1
Order By: Relevance
“…Although many disease-causing mutations result in protein misfolding, the misfolding typically alters function, assembly, or subcellular trafficking; protein topology is not affected (17). Recently, using an in vitro bacterial protein leader peptidase (Lep) translation system, Milenkovic et al (18) suggested that mutations in the macular degeneration-associated bestrophin-1 protein inhibit transmembrane segment insertion. However, we are only aware of one mutation proven to alter topology in a native protein; the prion-protein (PrP) A117V mutation found in GerstmannStraussler-Scheinker disease increases the fraction of the transmembrane form of the PrP (19).…”
Section: Discussionmentioning
confidence: 99%
“…Although many disease-causing mutations result in protein misfolding, the misfolding typically alters function, assembly, or subcellular trafficking; protein topology is not affected (17). Recently, using an in vitro bacterial protein leader peptidase (Lep) translation system, Milenkovic et al (18) suggested that mutations in the macular degeneration-associated bestrophin-1 protein inhibit transmembrane segment insertion. However, we are only aware of one mutation proven to alter topology in a native protein; the prion-protein (PrP) A117V mutation found in GerstmannStraussler-Scheinker disease increases the fraction of the transmembrane form of the PrP (19).…”
Section: Discussionmentioning
confidence: 99%
“…3A) (Tsunenari et al, 2003;Milenkovic et al, 2007). To identify the region of hBest1 responsible for inhibition of Ca V 1.3, we cotransfected Ca V 1.3 subunits with cDNAs corresponding to either the C-terminal (CT ) or N-terminal (NT 1-289 ) part of hBest1.…”
Section: Expression Of Wt Hbest1 In Hek293 Cells Induced Ca 2ϩ -Depenmentioning
confidence: 99%
“…Two differing topology models have been proposed for Best channels (15,23). For simplicity, we numbered the domains according to the recent Milenkovic model (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…hBest1 contains six hydrophobic segments (S1-S6), with both N and C termini residing inside the cell. Two topology models have been proposed for hBest1 (15,23). In the first model, S1, S2, S4, and S6 traverse the membrane, whereas S3 is intracellular and S5 forms a reentrant loop from outside (15).…”
mentioning
confidence: 99%
See 1 more Smart Citation